EUS‐guided cholecystoduodenostomy using novel dumbbell‐shaped fully covered metal stent (with video). (9th April 2021) - Atalla, Hassan; Shiomi, Hideyuki; Nakano, Ryota; Sakai, Arata; Kobayashi, Takashi; Masuda, Atsuhiro; Kodama, Yuzo
Abstract : Highlight Atalla and colleagues present a novel dumbbell‐shaped fully covered self‐expandable metal stent which, with its anti‐migration property and relatively lower cost, is a feasible and cost‐effective option as an alternative to lumen‐apposing metal stents for endoscopic ultrasound‐guided transduodenal gallbladder drainage for acute cholecystitis in patients who are ineligible for surgery.